2010
DOI: 10.1007/s10811-010-9603-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of N supply on the accumulation of photosynthetic pigments and photoprotectors in Gracilaria tenuistipitata (Rhodophyta) cultured under UV radiation

Abstract: We have studied the effects of nitrate supply under photosynthetic active radiation (PAR) plus ultraviolet radiation (UVR) exposure on photosynthetic pigments (chlorophyll a and carotenoids), photoprotective UV screen mycosporine-like amino acids (MAAs), and photosynthetic parameters, including the maximum quantum yield (F v /F m ) and electron transport rate (ETR) on the red agarophyte Gracilaria tenuistipitata. Apical tips of G. tenuistipitata were cultivated under ten different concentrations of NO 3 − for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(43 citation statements)
references
References 67 publications
3
35
0
5
Order By: Relevance
“…The NPQ, an important strategy for phytoplankton to rapidly (seconds to minutes) regulate photochemistry, is one of the first lines of defense that Kashino et al (2002) and Fujiki et al (2003) also indicated that the NPQ process is of importance to maintain the photosynthetic activity of phytoplankton. On the other hand, the substances, that need N for their synthesis, e.g., UV-screening compounds like mycosporine-like amino acids were recorded to increase with increasing nitrogen levels (Litchman et al 2002, Korbee et al 2010, Barufi et al 2011 and might also attribute to the higher UVR sensitivity in LN-than in HN-grown cells. The diatom grown under N-limited condition exhibited higher sensitivity to UVR than that grown under N-replete condition, based on the changes in the photochemical quantum yield and NPQ, which indicates that the N limitation exacerbates the effects of UVR on its photosynthetic performance and stimulate its NPQ.…”
Section: Discussionmentioning
confidence: 99%
“…The NPQ, an important strategy for phytoplankton to rapidly (seconds to minutes) regulate photochemistry, is one of the first lines of defense that Kashino et al (2002) and Fujiki et al (2003) also indicated that the NPQ process is of importance to maintain the photosynthetic activity of phytoplankton. On the other hand, the substances, that need N for their synthesis, e.g., UV-screening compounds like mycosporine-like amino acids were recorded to increase with increasing nitrogen levels (Litchman et al 2002, Korbee et al 2010, Barufi et al 2011 and might also attribute to the higher UVR sensitivity in LN-than in HN-grown cells. The diatom grown under N-limited condition exhibited higher sensitivity to UVR than that grown under N-replete condition, based on the changes in the photochemical quantum yield and NPQ, which indicates that the N limitation exacerbates the effects of UVR on its photosynthetic performance and stimulate its NPQ.…”
Section: Discussionmentioning
confidence: 99%
“…First, the high amount of PE in G. birdiae cultivated under BL could act as a system of energy dissipation, together with a possible xanthophyll cycle, a phenomenon which has been related to energy dissipation (Demmig-Adams 2003). The occurrence of this cycle in G. birdiae was suggested by Ursi et al (2003), and an incomplete xanthophyll cycle was proposed for G. tenuistipitata by Barufi et al (2011). A second photoprotective mechanism involves the position of different phycobiliproteins in the phycobilisome.…”
Section: Discussionmentioning
confidence: 99%
“…Di bawah cekaman ultraviolet tanaman mengorbankan kloroplasnya dalam rangka melindungi sel. Iradiasi ultraviolet kemungkinan mempengaruhi pigmen fotosintesis, di samping itu juga menghambat sintesisnya atau mempengaruhi enzim-enzim yang terlibat dalam jalur sintesis klorofil (Barufi et al, 2010).…”
Section: Kadar Klorofilunclassified
“…Walau demikian, tanaman perlakuan ini ternyata mampu untuk melakukan perbaikan. Kelompok tanaman anyelir yang disimpan pada cahaya ternyata dapat melakukan pemulihan sendiri dengan bantuan cahaya yang dikenal dengan metode fotoreaktivasi (Barufi et al, 2010). Bahkan pada tanaman yang disimpan di tempat gelap pun juga muncul tunas aksilernya.…”
Section: Kadar Klorofilunclassified